Leben machen Die Zoëpolitik der synthetischen Biologie - Müller, Martin (De Gruyter, 2023)
Synthetic biology attempts to redesign entire species and intervenes in the human germline with CRISPR. Martin Müller　problematizes the technologies and discourses of this Promethean biology and situates them in a critical genealogy of zoëpolitics, in which the "vivification of power" around 1800 and the "molecular revolution" of the 20th century appear as previous stages of escalation in a turbulent history of the "will to make life".